Integrating gendered knowledge into banana breeding - Marimo, Pricilla; Tumuhimbise, Robooni (Bioversity International, 2018)
This presentation was given during a webinar on May 17, 2018. This is the first of these presentations given by Pricilla Marimo (Bioversity International) and Robooni Tumuhimbise (NARO)